Ague (2021)
The heritage of the weaving of the traditional Kankuama backpack, whose knowledge was transmitted for generations within my family circle, brings with it countless stories, of oral tradition, which set in me the desire to unveil this knowledge of the environment inhabited by those who they preceded me In equal measure, moving to the City of Bogotá implies the acquisition of an identity conditioned by the social dynamics of the city; Faced with this constant process of alienation, I ask myself simultaneously about the before and after, my memories and knowledge, and in this constant questioning I suspect both of one and the other. Therefore, the need arises to go back to the environment and seek in it a critical and reflective analysis regarding weaving and random provocation: weaving as Las Moiras do, or better yet, as my Great-grandmother did; to be able to find in that vital act the consolidation of the self.